PENGARUH CIRCUIT TRAINING TERHADAP DAYA TAHAN ANAEROBIK TIM FUTSAL PUTRI ILMU KEOLAHRAGAAN UNTAN - Willanda, Efipania Cega; Simanjuntak, Victor; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem of this research was whether there is influence of circuit training on the anaerobic endurance of the UNTAN women's futsal team. This study aimed to determine the effect of circuit training on the anaerobic endurance of UNTAN women's futsal team. The method in this study used an experimental method in the form of Pre Experimental Design. The population in this study was the UNTANÂ women's futsal team which totaled 13 students. The number of samples in this studyamounted to 13 students. The instrument used was RAST. Data analysis using t test analysis (influence test). Based on the calculation of the data obtained the results of t test (influence test), t count of 2.749 and ttable of 1,782 can be concluded t count> t table (2,749> 1,782). It can be concluded, there is an influence from circuit training on the anaerobic endurance of UNTAN women's futsal team. As for the percentage increase after being given a circuit training treatment of 22%.Keywords: Anaerobic endurance, Circuit training, Futsal